2015
DOI: 10.1371/journal.pone.0133840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Doses (5-40 cGy) of Gamma-irradiation on Lifespan and Stress-related Genes Expression Profile in Drosophila melanogaster

Abstract: Studying of the effects of low doses of γ-irradiation is a crucial issue in different areas of interest, from environmental safety and industrial monitoring to aerospace and medicine. The goal of this work is to identify changes of lifespan and expression stress-sensitive genes in Drosophila melanogaster, exposed to low doses of γ-irradiation (5 – 40 cGy) on the imaginal stage of development. Although some changes in life extensity in males were identified (the effect of hormesis after the exposure to 5, 10 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 109 publications
3
28
0
Order By: Relevance
“…These stimuli include ultraviolet radiation, magnetic and electromagnetic fields, microwaves, ultrasound, and low-dose irradiation. 16 23 In silkworms, shortening of the embryogenesis period by several hours was reported after chronic radiation, 100, 1000, and 4000 times exceeding the natural background radiation. 20 The group also reported an increase in the mass of larvae after a single dose of 2 Gy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These stimuli include ultraviolet radiation, magnetic and electromagnetic fields, microwaves, ultrasound, and low-dose irradiation. 16 23 In silkworms, shortening of the embryogenesis period by several hours was reported after chronic radiation, 100, 1000, and 4000 times exceeding the natural background radiation. 20 The group also reported an increase in the mass of larvae after a single dose of 2 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 6 , 9 11 In various organisms including mammalians, insects, and plants, beneficial effects of low-dose irradiation have been reported. 16 23 Elongation of the life span of irradiated flour beetles ( Tribolium ) was reported more than 40 years ago, 16 and thereafter, the data showing biphasic responses of living organisms to irradiation (ie, beneficial effects at low doses and toxic or harmful effects at high doses) have been accumulating. However, more well-controlled laboratory studies are warranted to clarify the very important issue of the effect of low-dose radiation and to examine the adequateness of the LNT concept.…”
Section: Introductionmentioning
confidence: 99%
“…Stress response on the molecular level is dose-specific. Dose may influence the effects of ionizing radiation [ 30 ]. Low radiation (20-75 cGy) produces minimal cluster damages and breaks of double-stranded DNA, with the main effect related to the induction of active oxygen forms [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms behind irradiation-mediated reduction of Plasmodium infection are not yet clear but interferences with mosquito immunity, microbiota and/or parasite infectivity mechanisms are likely. Although it is well-known that irradiation causes DNA damages, oxidative stress, and changes in gene expression including immune genes (Zhikrevetskaya et al ., 2015), its impact on insect host-pathogen interactions remain generally unclear (Morley, 2012). While a study found that irradiated Tephritidae flies displayed damaged midgut and peritrophic membrane resulting in decreased bacterial growth (Lauzon and Potter, 2012), irradiated Spodoptera butterflies showed increased susceptibility to a nucleopolyhedrosis virus (Sayed and El-Helaly, 2018).…”
Section: Discussionmentioning
confidence: 99%